Avaliação da fibra da bucha vegetal (Luffa cylindrica) e das folhas de taboa (Typha angustifolia L.) como materiais adsorventes para a remoção do agrotóxico tebuconazol de água contaminada - (:unkn) unknown (Universidade Federal de Goiás, 2019)
Agrochemicals are industrialized products made up of a broad junction of chemicals used to combat pest resistance in plantations. The high consumption and the inappropriate disposal of these products can generate great environmental impacts. Adsorption processes employing alternative materials have been evaluated to remove them from the environment, especially from water sources for human consumption. In this work, the adsorption capacity of the materials: bush (Luffa cylindrica) and taboa (Typha angustifolia L.) was evaluated for the removal of the tebuconazole pesticide from aqueous medium. The analytical methodology used to quantify the pesticide in the solution, after the removal, was High Performance Liquid Chromatography with UV-vis detector (HPLC-UV). The values of LD and LQ in the chromatographic method were 0.01 mg L-1 and 0.10 mg L-1 , respectively. The materials were characterized by the FTIR technique, being observed in both materials the presence of functional groups characteristic of lignocellulosic compounds. The micrographs (SEM) indicated the heterogeneity and irregularity of the surface in both materials. The pH at the zero charge point (pHPCZ) was 6.15 for bush (Luffa cylindrica) and 6.62 for taboa (Typha angustifolia L.). The ability to remove tebuconazole from the aqueous medium by the materials was evaluated as a function of the adsorbent dosage, contact time and concentration of the pesticide. The dosages of 20 and 10 g L-1 were used in the adsorption tests with the bush (Luffa cylindrica) and taboa (Typha angustifolia L.), respectively. The kinetic study showed that the adsorption equilibrium was obtained after 40 minutes of contact and the experimental data were better adjusted by the Avrami model, for both materials. Regarding the study of tebuconazole concentration, it was observed that the removal is little influenced by the increase in tebuconazole concentration in the medium, remaining relatively constant in the concentration range evaluated, for both materials. The experimental data were well adjusted by all models of isotherms evaluated (Langmuir, Freundlich and Sips), with R 2> 0.99. The maximum adsorption capacity (Qmax) of tebuconazole was 8.5651 mg g-1 for bush (Luffa cylindrica) and 13.6419 mg g-1 for taboa (Typha angustifolia L.).The use of the adsorbents to remove the pesticide in natural water sample presented results very similar to those observed when using deionized water, showing that the removal efficiency of these materials is not affected by the type of aqueous matrix. The alternative column adsorption process showed satisfactory removal results (~ 51% removal for bush and ~ 75% removal with taboa), in a significantly shorter time (3-4 min) in relation to the batch process (40 min). Thus, it can be concluded that the adsorbent materials evaluated, bush (Luffa cylindrica) and the taboa (Typha angustifolia L.) can be used for the removal of the tebuconazole pesticide from aqueous medium.
Evaluation of the fiber of the vegetal bush (Luffa cylindrica) and the leaves of taboa (Typha angustifolia L.) as adsorbent materials for the removal of the tebuconazole pesticide from contaminated water
Keywords: Adsorção; Agrotóxico; Tebuconazol; Cromatografia líquida; Adsorvente alternativo; Bucha (Luffa cylindrica); Taboa (Typha angustifolia L.); Adsorption; Pesticide; Tebuconazole; Liquid chromatography; Alternative adsorbent; Bush (Luffa cylindrica); CIENCIAS EXATAS E DA TERRA::QUIMICA